Endochondral ossification of hindlimbs in embryonic development of Japanese Quail (Coturnix japonica) - Xuan Li; Yuxin Zhang; Hongfeng Zhao (Avian Research, 2024)
The endochondral ossification of hindlimb is essential to a bird's ability to stand, walk and fly. Most hindlimb is ossified in the embryos before hatching in precocial birds. However, the molecular mechanisms of hindlimb ossification in birds is still unclear. Therefore, we tried to examine the process of hindlimb ossification and its molecular regulation by using an animal model—Japanese Quail (Coturnix japonica). We selected four critical stages (Embryo Day: E6, E8, E12 and E16) of skeletal development of embryonic quails for hindlimb skeleton staining to show the process of endochondral ossification and to examine the molecular regulation of endochondral osteogenesis by RNA-Seq analysis. The results showed that ossification became increased with embryonic development and most hindlimb was ossified before hatching. RNA-Seq analysis revealed that various signaling pathways were involved with endochondral ossification with thyroid hormone signaling and WNT signaling pathway particularly enriched. Moreover, the expression levels of 42 genes were continuously upregulated and 14 genes were continuously downregulated from E6 to E16. The present study might provide new insights into complex molecular mechanisms in regulation of endochondral ossification.